The next WHO director-general's highest priority: a global treaty on the human right to health - Gostin, Lawrence O.; Friedman, Eric A.; Buss, Paulo Marchiori; Chowdhury, Mushtaque Raza; Grover, Anand; Heywood, Mark J.; Kanchanachitra, C.; Leung, Gabriel M.; Mackay, Judith Mary; Matsoso, Precious; Møgedal, Sigrun M.; Omaswa, Francis G.; et al. (© 2016 Elsevier Ltd., 2018)
This article was published in the The Lancet Global Health [© 2016 Elsevier Ltd] and the definitive version is available at: http://doi.org/10.1016/S2214-109X(16)30219-4 The Journal's website is at: https://linkinghub.elsevier.com/retrieve/pii/S2214109X16302194